(untitled) (Physical Education, Health and Social Sciences, 2025)
Polycystic Ovary Syndrome (PCOS) is a multifactorial disorder influenced by genetic, environmental, and lifestyle factors. It often leads to various reproductive and metabolic complications, including menstrual irregularities, obesity, and infertility, with growing concerns about its association with miscarriages. This study aims to assess the prevalence of PCOS-related miscarriages and explore potential contributing factors among women in a specific population. Data were collected from 400 participants, focusing on demographic, dietary, and clinical characteristics. Results indicate that a significant percentage of women with PCOS experience reproductive challenges, with factors such as obesity, lack of exercise, and family history playing a critical role. These findings highlight the importance of early diagnosis and lifestyle modifications in managing PCOS and reducing the risk of miscarriages. The study provides valuable insights into the regional prevalence and impact of PCOS, which can aid future research and interventions aimed at improving women’s reproductive health.